Canon Law at the Universities and Academies in Warsaw in the Context of Socio-Political Changes in the 19th Century.: A Contribution to the Historical Analysis of the Issue - Ryguła, Piotr (Prawo Kanoniczne, 2025)
The history of canon law taught academically in the 19th-century Warsaw is inextricably linked with the history of the first and all subsequent universities in the city, which are widely regarded as the direct predecessors of the modern University of Warsaw. This article presents a historical analysis of the teaching of this subject at the faculties of law and theology (if such faculties were established), at the School of Law during the Duchy of Warsaw, and later in the Kingdom of Poland at the Royal University of Warsaw (1816–1831), at the Main School in Warsaw (1862–1869), and at the Clerical Academy in Warsaw. The history of lectures and lecturers in canon law is presented against the backdrop of socio-political changes that influenced not only the inclusion of this subject in university curricula but also its thematic scope and the decisions concerning the appointment of individual lecturers.